'I place form before content' – an interview in 2009 with Alun Munslow. Issue 3 (3rd July 2021) - Erős, Vilmos
ABSTRACT: The following interview with the former editor-in-chief of Rethinking History, the recently deceased Professor Alun Munslow was published in Hungarian in the Hungarian historical journal Aetas in 2009. In the interview Professor Munslow discusses his family background, his career, scholarly and educational/teaching experiences, the birth and concept of the journal Rethinking History, his 'scientific' credo, futures plans, and so on. As far as the author of these present lines (and the interviewer) knows, Professor Alun Munslow never gave an interview in English (2011), and the original text of this discussion will help get to know him and his ideas a little bit better. The text likewise serves to commemorate him as one of the 'founding fathers' of Rethinking History . It is also relevant given the fact that Professor Munslow regarded the interview as a highly significant genre, a kind of 'ego-history', in which historians can even better position themselves and their approach to history.